Brain mural cell loss in the parietal cortex in Alzheimer's disease correlates with cognitive decline and TDP‐43 pathology. (11th February 2020) - Bourassa, P.; Tremblay, C.; Schneider, J. A.; Bennett, D. A.; Calon, F.
Abstract : Aims: Brain mural cells (BMC), smooth muscle cells and pericytes, interact closely with endothelial cells and modulate numerous cerebrovascular functions. A loss of BMC function is suspected to play a role in the pathophysiology of Alzheimer's Disease (AD). Methods: BMC markers, namely smooth muscle alpha actin (α‐SMA) for smooth muscle cells, as well as platelet‐derived growth factor receptor β (PDGFRβ) and aminopeptidase N (ANPEP or CD13) for pericytes, were assessed by Western immunoblotting in microvessel extracts from the parietal cortex of 60 participants of the Religious Orders study, with ages at death ranging from 75 to 98 years old. Results: Participants clinically diagnosed with AD had lower vascular levels of α‐SMA, PDGFRβ and CD13. These reductions were correlated with lower cognitive scores for global cognition, episodic and semantic memory, perceptual speed and visuospatial ability. In addition, α‐SMA, PDGFRβ and CD13 were negatively correlated with vascular Aβ40 concentrations. Vascular levels of BMC markers were also inversely correlated with insoluble cleaved phosphorylated transactive response DNA binding protein 43 (TDP‐43) (25 kDa) and positively correlated with soluble cleaved phosphorylated TDP‐43 (35 kDa) in cortical homogenates, suggesting strong association between BMC loss and cleaved phosphorylated TDP‐43 aggregation. Conclusions: The results of this study highlight a loss of BMC in AD. The associations between α‐SMA, PDGFRβ and CD13 vascular levels with cognitive scores, TDP‐43 aggregation and cerebrovascular accumulation of Aβ in the parietal cortex suggest that BMC loss contributes to both AD symptoms and pathology, further strengthening the link between cerebrovascular defects and dementia.